Associations of self-reported skin symptoms with age, sex, and living with a partner: Findings from a representative survey in view of the biomedical and the biopsychosocial model - Reich, Hanna; Gieler, Uwe; Braehler, Elmar; Kupfer, Joerg (Frontiers in Medicine, 2023)
Social and demographic characteristics are crucial determinants of health. The objective of this contribution is to study the associations of skin symptoms and sociodemographic variables in the general population, and to discuss these findings in view of the biomedical and the biopsychosocial models of skin diseases. A national face-to-face household survey with a representative samples of the German general population assessed 19 self-reported skin symptoms (N=2,487). Associations with age, sex, and living situation (alone vs. with partner) were analyzed using logistic regression analyses. The frequencies of pimples and biting of the nails decreased by approximately 30% per age decade, and oily skin, the feeling of disfigurement, excoriations, and sun damages decreased by 7-15% per age decade. Sensitive skin and dryness were approx. twice as likely in females than in males. Dryness of the skin and excoriations were more frequent in participants living without a partner. The biomedical model explains some of the findings well (e.g., reduction of pimples with age). The interpretation of other results is facilitated by the biopsychosocial model (e.g., reduction of sun damages with age). This suggests a stronger integration of psychological and social factors into the understanding and treatment of symptoms of the skin.